Prevalence, causes and outcomes of hospital admissions in Mongolia: a national registry-based descriptive analysisResearch in context - Altanchimeg Sainbayar; Ganbold Lundeg; Naranpurev Mendsaikhan; Jens Meier; Martin W. Dünser (The Lancet Regional Health. Western Pacific)
Summary: Background: No systematic data on the prevalence of, reasons for, and outcomes of hospital admissions in Mongolia are currently available. Methods: In a descriptive analysis, the Mongolian National Hospital Data registry was screened for all hospital admissions in adults from 1 January 2019 to 31 December 2023. The endpoints were the prevalence of and most common reasons for hospital admission, the length of hospital stay, and the hospital mortality rate. Descriptive methods, Chi-square tests, Mann-Whitney-U-tests, and ANOVA on ranks were used for data analysis. Findings: 3,449,083 cases were analysed. The median prevalence of hospital admissions per 100,000 population per year was 20,242 (IQR, 19,412–20,778). The most common main diagnoses were COVID-19 (8.7%; 299,409/3,449,083), chronic tubulo-interstitial nephritis (6.7%; 230,244/3,449,083), chronic arterial hypertension (2.5%; 86,213/3,449,083), chronic ischaemic heart disease (2.3%; 80,071/3,449,083), nerve root/plexus disorders (2.3%; 79,341/3,449,083), hypertensive heart disease (2.1%; 73,597/3,449,083), and lower back pain (1.8%; 60,614/3,449,083). The median length of hospital stay was 7 days (IQR, 6–9) and the hospital mortality rate was 0.66% (22,683/3,449,083). Differences in all endpoints were found between female and male participants, the periods before, during, and after the COVID-19 pandemic, regions of residence, seasons of admission, levels of admission hospitals, and public and private hospitals. Interpretation: During a five-year period including the COVID-19 pandemic, the prevalence of hospital admissions in Mongolian adults was high during the study period. An analysis of the most common diagnoses leading to hospital admission suggested that many diagnoses could be managed without hospital admission in outpatient or primary care settings. Funding: Institutional funding (Mongolian National University of Medical Sciences and the Johannes Kepler University).